2015
DOI: 10.1021/acs.langmuir.5b01935
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Surface and Intercalated Impurities in Graphene by LEIS

Abstract: Low-energy ion scattering (LEIS) is known for its extreme surface sensitivity, as it yields a quantitative analysis of the outermost surface as well as highly resolved in-depth information for ultrathin surface layers. Hence, it could have been generally considered to be a suitable technique for the analysis of graphene samples. However, due to the low scattering cross section for light elements such as carbon, LEIS has not become a common technique for the characterization of graphene. In the present study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…LEIS is known for its extreme surface sensitivity and possibility to provide quantitative composition of the outermost surface layer [40]. It has also proved its ability in detailed characterization of graphene on silica substrate [41]. We have used a 3-keV He ion beam at a scattering angle of 145° to obtain a spectrum of the FeRh sample covered by graphene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LEIS is known for its extreme surface sensitivity and possibility to provide quantitative composition of the outermost surface layer [40]. It has also proved its ability in detailed characterization of graphene on silica substrate [41]. We have used a 3-keV He ion beam at a scattering angle of 145° to obtain a spectrum of the FeRh sample covered by graphene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observed change of the La signal by 2.5 times in absence of other elements is very intriguing and is unusual for LEIS. There are only a few of matrix effects which have a stronger influence on the signal, for example matrix effect in graphitic carbon [10]. Therefore a logical check if this behavior can be explained by small quantities of other elements was performed, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Matrix effects can only exist if more than one element is present (carbon with its vastly different valence zone structure of allotropes is again an exception [10]). But LEIS spectra of fresh La film show no sign of contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this is important for certain carbonaceous nanostructured surfaces, wherein the irradiation damage can be important for certain irradiation conditions. Recently [32], it has been shown that the technique is capable of checking the purity of graphene surfaces, demonstrating the benefits of the technique in screening the quality of the graphene during its fabrication process.…”
Section: Introductionmentioning
confidence: 99%